George D. Aiken proclamation - Aiken, George D. (George David), 1892-1984.
Proclamation (1937 October 26) of Aiken, governor of Vermont, commissioning the seal of Vermont.
U.S. senator from and governor of Vermont.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Vermont -- Seal; Governors -- Vermont; Senators, U.S. Congress -- Vermont